Mechanisms of exertional dyspnoea in symptomatic smokers without COPD. Issue 3 (4th August 2016) - Elbehairy, Amany F.; Guenette, Jordan A.; Faisal, Azmy; Ciavaglia, Casey E.; Webb, Katherine A.; Jensen, Dennis; Ramsook, Andrew H.; Neder, J. Alberto; O'Donnell, Denis E.
Dyspnoea and activity limitation can occur in smokers who do not meet spirometric criteria for chronic obstructive pulmonary disease (COPD) but the underlying mechanisms are unknown. Detailed pulmonary function tests and sensory–mechanical relationships during incremental exercise with respiratory pressure measurements and diaphragmatic electromyography (EMGdi ) were compared in 20 smokers without spirometric COPD and 20 age-matched healthy controls. Smokers (mean±sd post-bronchodilator forced expiratory volume in 1 s (FEV1 )/forced vital capacity 75±4%, mean±sd FEV1 104±14% predicted) had greater activity-related dyspnoea, poorer health status and lower physical activity than controls. Smokers had peripheral airway dysfunction: higher phase-III nitrogen slopes (3.8±1.8 versus 2.6±1.1%·L −1 ) and airway resistance (difference between airway resistance measured at 5 Hz and 20 Hz 19±11 versus 12±7% at 5 Hz) than controls (p<0.05). Smokers had significantly (p<0.05) lower peak oxygen uptake (78±40 versus 107±45% predicted) and ventilation (61±26 versus 97±29 L·min −1 ). Exercise ventilatory requirements, operating lung volumes and cardio-circulatory responses were similar. However, submaximal dyspnoea ratings, resistive and total work of breathing were increased in smokers compared with controls (p<0.05); diaphragmatic effort (transdiaphragmatic pressure/maximumal transdiaphragmatic pressure) and fractional inspiratory neural drive to the diaphragm (EMGdi /maximal EMGdi ) were also increased (p<0.05) mainly reflecting the reduced denominator. Symptomatic smokers at risk for COPD had greater exertional dyspnoea and lower exercise tolerance compared with healthy controls in association with greater airways resistance, contractile diaphragmatic effort and fractional inspiratory neural drive to the diaphragm. Exertional dyspnoea in smokers without COPD is linked to higher inspiratory neural drive to the crural diaphragm http://ow.ly/e9Z7302uFM6